Efeito do emprego do frio no perfil sensorial do camarão marinho Litopenaeus vannamei (Boone, 1931) - Queiroga, Inês Maria Barbosa Nunes (2013)
In recent years, an increasing number of people have entered the fish in their diets as a healthy alternative to protein intake. Among the seafood, shrimp is one of the most important commercial products. Being a highly perishable food, some conservation methods are being researched in order to prolong their shelf life, in this work, it was investigated whether the low temperatures. The sample consisted of farmed shrimp species Litopenaeus vannamei (100-120 pieces / kg) contained in packs of 200g with four packages by treatment with the filet shrimp, chilled at 0 ± 2 ° C, divided into three parts, the first packaged packaged with 1% sodium metabisulfite, and modified atmosphere in concentrations of O2 + 0 100% CO2, 75% O2 + 25% CO2 + 60% O2 + 40% CO2, 50% O2 + 50% CO2, the second packaged without 1% sodium metabisulfite and modified atmosphere gases at the same concentrations above, both with analysis at 0, 3, 6 and 9 days storage and subjected to freezing to third subdivided into three treatments, domestic freezer (CFD) to -18 ° C. Liquid nitrogen (CNL) at -86 ° C and freeze tunnel (CTC) at -35 ° C, analysis at 0, 30, 60 and 90 days of storage. We conducted physical and chemical analysis of pH, weight loss after cooking, water holding capacity, texture, color, total volatile bases and thiobarbituric acid reactive substances, and the sensory analysis was elected as the Quality Index Method ( MIQ) and Descriptive Analysis (AD), concluding that the weather influenced the physical, chemical and sensory cold shrimp, demonstrating an increase in all the aforementioned parameters. There was a high correlation between the Quality Index (QI) and time of storage. The maximum storage time in nine days or samples chilled, packed in a modified atmosphere and treated with 1% sodium metabisulfite, six days for samples chilled, packed in a modified atmosphere without additive, and 90 days for samples frozen, was estimated based on Descriptive Analysis and Quality Index Method.